Keefektifan Layanan Bimbingan Kelompok dengan Teknik Sodiodrama untuk Meningkatkan Kepercayaan Diri - Haryanti, Desy Tri; sugiyo, sugiyo (Universitas Negeri Semarang, 2016)
Phenomenon in class IX C SMP Islam Ungaran shows a lack of confidence shown by feeling nervous when advanced in front of the class that looks shaky hands and legs move students who are hesitant, embarrassed when dealing with the crowds, there are students who do not venture out such class to the cafeteria because they feel less attractive appearance. Efforts are being made to reduce this problem is to provide technical guidance to the group sociodramas. The purpose of this study was to obtain empirical data on the effectiveness of the group with technical guidance services sociodramas to increase self-confidence. The population in this study were students of SMP Islam Ungaran IX C class consists of 24 students and a sample of 10 students were taken using purposive sampling. Data collection method used is the psychological scale. Data were analyzed using Wilcoxon matched pairs test. The results showed before obtaining services group with technical guidance sociodramas, the confidence of students included in the criteria are, and after obtaining technical guidance services group with confidence sociodramas criteria, students become high. Wilcoxon matched pairs test results show T (0) and T_tabel 5% (8) so that T_hitung <T_ (table) (0 <8) which means H_a received and H_0ditolak. It shows that the group with technical guidance services sociodramas effective to increase self-confidence.